The Nquiry Learning Strategy on Skills of Science Process and Class IV Learning Motivationstate in SDN 24 Elementary School Singgalang - Vivi Lusidawaty; Yanti Fitria; Yalvema Miaz; Risda Amini (Postgraduate School, Universitas Negeri Padang, 2019)
This study aims to describe the implementation of inquiry learning strategies to improve learning motivation and science process skills of students in grade IV of Ginggong Singgalang 24 Elementary School. This study is a class action research which is a study developed jointly for researchers and decisions maker about variables that are manipulated and can be used to make improvements. Repairs are carried out with two cycles, namely cycle 1 and cycle 2. Data from research results can be grouped into two, namely quantitative and qualitative data. Quantitative data, namely numerical data, are qualitative data in the form of descriptive. As the subjects in this study were teachers and fourth grade students of SDN 24 Ganting Singgalang District X Koto Tanah Datar District, amounting to 30 people consisting of 13 male students and 17 female students. The results showed that the average value of students in cycle 1 was 72 experiencing an increase in cycle 2, namely 87. The percentage of students' mastery learning in the first cycle was 62% of students obtaining complete grades, while in the second cycle 93% of students obtained completing grades. Thus, there was an increase of as much as 31%. Student learning motivation with the implementation of inquiry learning strategies in class IV of Ginggong Singgalang 24 Elementary School was stated with more than 50% of students who agreed, 57% stated Strongly Agree and 33% agreed. Meanwhile, 7% said that they were Doubtful and 3% stated that they did not agree.